Phenomics and Genomics Reveal Adaptation of Virgibacillus dokdonensis Strain 21D to Its Origin of Isolation, the Seawater-Brine Interface of the Mediterranean Sea Deep Hypersaline Anoxic Basin Discovery - Zeaiter, Zahraa; Marasco, Ramona; Booth, Jenny M.; Prosdocimi, Erica M.; Mapelli, Francesca; Callegari, Matteo; Fusi, Marco; Michoud, Grégoire; Molinari, Francesco; Daffonchio, Daniele; Borin, Sara; Crotti, Elena (Frontiers in Microbiology, 2019)
The adaptation of sporeformers to extreme environmental conditions is frequently questioned due to their capacity to produce highly resistant endospores that are considered as resting contaminants, not representing populations adapted to the system. In this work, in order to gain a better understanding of bacterial adaptation to extreme habitats, we investigated the phenotypic and genomic characteristics of the halophile Virgibacillus sp. 21D isolated from the seawater-brine interface (SBI) of the MgCl2-saturated deep hypersaline anoxic basin Discovery located in the Eastern Mediterranean Sea. Vegetative cells of strain 21D showed the ability to grow in the presence of high concentrations of MgCl2, such as 14.28% corresponding to 1.5M. Biolog phenotype MicroArray (PM) was adopted to investigate the strain phenotype, with reference to carbon energy utilization and osmotic tolerance. The strain was able to metabolize only 8.4% of 190 carbon sources provided in the PM1 and PM2 plates, mainly carbohydrates, in accordance with the low availability of nutrients in its habitat of origin. By using in silico DNA-DNA hybridization the analysis of strain 21D genome, assembled in one circular contig, revealed that the strain belongs to the species Virgibacillus dokdonensis. The genome presented compatible solute-based osmoadaptation traits, including genes encoding for osmotically activated glycine-betaine/carnitine/choline ABC transporters, as well as ectoine synthase enzymes. Osmoadaptation of the strain was then confirmed with phenotypic assays by using the osmolyte PM9 Biolog plate and growth experiments. Furthermore, the neutral isoelectric point of the reconstructed proteome suggested that the strain osmoadaptation was mainly mediated by compatible solutes. The presence of genes involved in iron acquisition and metabolism indicated that osmoadaptation was tailored to the iron-depleted saline waters of the Discovery SBI. Overall, both phenomics and genomics highlighted the potential capability of V. dokdonensis 21D vegetative cells to adapt to the environmental conditions in Discovery SBI.